Development prospects of food markets in Andijan province - Bahodirjon Z. Nosirov; Akmal A. Ergashev; Dilobar T. Islamova (Агентство перспективных научных исследований (АПНИ), 2020)
The food crisis requires urgent action, both at the national level and around the world, and the development of a long-term strategy to combat hunger. Market infrastructure plays an important role in the formation of the regional food market. The main pillars of the market infrastructure are the organizational base, which includes wholesale and retail trade networks, exchanges and dealers, as well as the material base, which includes warehouses, transport and marketing services. The article discusses the ways of developing the food market in the Andijan province. Recommended concept of regional market management provides regional authorities with a long-term strategy and identifies possible alternatives for its implementation. Using it, you can substantiate the definition of ways to form developed market relations; determine socio-economic, investment and environmental parameters for the development of regional markets in the future and compare them with real opportunities; system of forms and methods of economic and legal management of regional markets of various types. Recommendations are given for improving the supply of livestock products to the food market of Andijan province.